Evaluating the scales used to diagnose incontinence-associated dermatitis: A systematic review - GÜLSEVEN KARABACAK, BİLGİ (My University, 2022)
OBJECTIVE: To investigate the scales used in the diagnosis of incontinenceassociated dermatitis (IAD), including the risk factors included in the scales, their reliability and validity, and in which patient groups the scales have been applied. DATA SOURCES: The relevant studies were screened retrospectively using five MeSH (Medical Subject Headings) keywords in various combinations. Seven international databases were screened between March and July 2019. In total, 2,908 studies published between 2009 and 2019 were evaluated. STUDY SELECTION: Inclusion criteria for studies were as follows: written in English, published between 2009 and 2019, and investigated a scale developed to diagnose IAD (quantitative studies, randomized controlled studies, or meta-analyses). Studies were excluded if they did not examine scales for diagnosing IAD or were not in English. Nine studies were included in this review: five studies on scale development, one scale revision, one scale reliability study, and two Turkish validity and reliability studies. DATA EXTRACTION: The study methods, sample characteristics, interventions, validity and reliability analyses, risk factors in the scales, and subdimensions of the scales were examined for each of the nine included studies. DATA SYNTHESIS: Study samples were composed of nurses, healthcare professionals, patients, or individuals living in a nursing home and ranged in size from 9 to 823 participants. Most data were collected from hospital-wide clinics. The scales used investigated redness, rash, skin loss, incontinence type, infection symptoms, skin color, edema, patient experience, pain, and perineal care habits. Both validity and reliability of the scales were examined in eight of the studies; in one study, only reliability was examined because the scale validity was shown in previous research. Moreover, sensitivity and specificity were indicated in one study. CONCLUSIONS: There are several competent scales in the literature with proven validity and reliability that can be used to diagnose IAD.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Dermatoloji; Cerrahi Tıp Bilimleri; Hemşirelik; Medicine; Health Sciences; Internal Medicine Sciences; Dermatology; Surgery Medicine Sciences; Nursing; DERMATOLOJİ; Klinik Tıp; Klinik Tıp (MED); HEMŞİRELİK; CERRAHİ; DERMATOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); NURSING; SURGERY; Yoğun Bakım Hemşireliği; Tıbbi ve Cerrahi Hemşirelik; Farmakoloji (hemşirelik); Annelik ve Ebelik; Onkoloji (hemşirelik); Hemşirelik (çeşitli); İleri ve Uzman Hemşirelik; Cerrahi; Asistan Hemşirelik; LPN ve LVN; Genel Hemşirelik; Acil Tıp Hemşireliği; Critical Care Nursing; Medical and Surgical Nursing; Pharmacology (nursing); Maternity and Midwifery; Oncology (nursing); Nursing (miscellaneous); Advanced and Specialized Nursing; Surgery; Nurse Assisting; LPN and LVN; General Nursing; Emergency Nursing; dermatitis; incontinence; methodological studies; risk assessment; skin care; INDEPENDENT RISK-FACTORS; CRITICALLY-ILL PATIENTS; NURSING-HOME RESIDENTS; SEVERITY INSTRUMENT; CATEGORY 2; RELIABILITY; NURSES; dermatitis; incontinence; methodological studies; risk assessment; skin care